Factors Influencing Measurement of Dynamic Elastic Modulus from Disk‑Shaped Concrete Specimen - Kim, Min Suk; Son, Jeong Jin; Chung, Chul-Woo; Lee, Chang Joon (International journal of concrete structures and materials, 2024)
The decrease in dynamic elastic modulus is a primary indicator of quantitative damage in concrete. To quantitatively assess depth-by-depth damage within a concrete structure, cylindrical specimens obtained through coring can be cut into disk specimens to measure the dynamic elastic modulus of concrete at each depth. To minimize external damage during coring, it is essential to extract cylinders with the smallest possible diameter. In addition, for higher resolution in depth-based damage assessment, creating disk specimens with the smallest possible thickness is necessary. However, there is no information available in the literature on experimental limitation of smallest possible diameter and thickness for dynamic elastic modulus of disk-shaped specimens. This study evaluated whether the dynamic modulus measured from various sizes of concrete disk specimens provided sufficient reliability compared to reference values obtained from cylinders. Moreover, the study examined how the presence of coarse aggregate and variation in the water–cement ratio significantly influenced the dynamic modulus measurement. In addition, test results from impulse excitation technique (IET) and impact resonance (IR) were compared to find a more reliable test method for dynamic elastic modulus of disk specimen. The experimental findings revealed that as the thickness-to-radius ratio of the disk specimens decreased, measured data variation increased. Mortar specimens without coarse aggregates showed less variability compared to concrete specimens, and the variation in dynamic modulus measured by IR was lower than that measured by IET.